Filosofi Astha Brata dalam Kepemimpinan Wakil Rakyat Menuju Indonesia Konstitusional dan Berkedaulatan Rakyat - Andina Elok Puri Maharani (Universitas Sebelas Maret, 2022)
This paper examines the leadership of the people's representatives towards a constitutional Indonesia and people's sovereignty in the perspective of the Astha Brata Philosophy. The issue in this paper is the crisis of leadership and public distrust of the performance of the people's representatives, in the context of this paper the members of the House of Representatives of the Republic of Indonesia. This crisis of confidence will gradually weaken democracy which is believed to be the way to prosperity based on people's sovereignty. The problems raised in this paper are why there are problems in the leadership of the people's representatives and how the Astha Brata philosophy is the answer in the leadership of the people's representatives towards a prosperous Indonesia with people's sovereignty. This type of research is doctrinal with a statutory approach, namely the 1945 Constitution of the Republic of Indonesia, legislation on elections and political recruitment, case approach and philosophical approach. The results of the study show that first, the root of the problem of the leadership of the people's representatives, namely an unhealthy political recruitment process, political education and regeneration that is not going well. Second, Astha Brata as a perfect philosophy to form leaders who have strong characters and provide protection towards a constitutional Indonesia and people's sovereignty.